Administrative Best Practices for Engaging New Faculty - Michael G Strawser; Russell Carpenter; Shanti Bruce; Kevin Dvorak (Academic Chairpersons Conference Proceedings, 2020)
Presenters and participants will discuss how Millennial faculty may a) change the higher education system; b) adapt their own internal wiring to fit higher education; and c) relate to faculty/staff of other generations. Participants will also address issues related to millennial faculty engagement and professional development, expectations of communication, and responses to campus sexual harassment.
Keywords: Faculty development; educational development; teaching and learning; mentorship